Poetry as window and mirror positioning the poet in Hellenistic poetry - Klooster, Jacqueline. (Mnemosyne, Supplements, 2011)
Hellenistic Poetry has enjoyed a notable re-appreciation in recent years and received ample scholarly discussion, especially focusing on its reception and innovation of Greek poetic tradition. This book wishes to add to our picture of how Hellenistic poetry works by looking at it from a slightly different angle. Concentrating on the interaction between contemporary poets, it attempts to view the dynamics of imitation and reception in the light of poetical self-positioning. In the courtly Alexandrian surroundings, choosing a poetic model and affiliation determines one's position in the cultural field. This book sets out to chart, not only the well-known complexities of handling the poetic past, but especially their relation to the poetic interaction of the Hellenistic, in particular Alexandrian poets.